Проблемы Качественного Преподавания Технических Дисциплин В Вузах Республики Узбекистан - Атаджанова Малика Зафар қизи (Academia One, 2025)
Modern challenges in the field of engineering education require a revision of traditional methods of teaching technical disciplines, especially in the context of rapidly developing scientific and technological progress. The article analyzes the key problems faced by higher education institutions of the Republic of Uzbekistan in the implementation of educational programs in the technical field. These problems include: a lack of modern laboratory facilities, weak practical focus of courses, a shortage of qualified personnel, an insufficient level of digitalization of the educational process, as well as limited access to international educational resources. Specific measures are proposed to improve the quality of training of engineers and technical specialists, including reforming curricula, improving the qualifications of teachers and expanding international cooperation
Keywords: educational process; research work; higher education